Extending the Performance Limit of Anodes: Insights from Diffusion Kinetics of Alloying Anodes. Issue 27 (28th December 2020) - Choi, Yong‐Seok; Scanlon, David O.; Lee, Jae‐Chul
Abstract: Alloying anodes have long attracted attention as promising candidate electrodes for application in grid‐level energy storage systems owing to their high energy capacity. Alloying anode‐based batteries, however, remain far from practical applications, which require several issues affecting cell performance to be addressed. The large volumetric expansion of anodes and associated phenomena that occur during battery cycling are the main reasons for the poor electrochemical performance of alloying anodes. These electrochemical behaviors of alloying anodes originate from the reactions between the unreacted anode material and inflowing carrier ions. Thus, the diffusion kinetics play a key role in determining the electrochemical properties of alloying anodes. Recent advances in analytical instruments and atomic simulations offer new approaches for interpreting anode performance. Beginning with a brief historical background, this review presents an overview of the origin of diffusion kinetics and how this concept has been extended to alloying anodes. Accordingly, the relationship between the diffusion kinetics and electrochemical performance of alloying anodes is discussed, combined with efficient strategies that can be adopted to improve electrochemical properties. Finally, a design overview of next‐generation alloying anodes that can extend the batteries' performance limit is proposed. Abstract : Alloying anodes, despite their large theoretical capacity, share common challenges related to poor cyclability/practical capacity/rate performance. From the perspective of diffusion kinetics, this review discusses the origin of the poor electrochemical performance of alloying anodes and proposes efficient strategies that can be adopted to design next‐generation alloying anodes and to extend the batteries' performance limit.